A review on Nazis' persuasive propaganda approaches in shaping the Germans mind / Wardatul Hayat Adnan - Hayat Adnan, Wardatul (Centre For Media And Information Warfare Studies, 2021)
The German Great Depression struck in late 1929, affecting Central Europe. The significant implications of this downturn include an increase in unemployment rates of more than 20% in Germany, Austria, and Poland. The German Weimar Republic was severely impacted by the slump when the Americans' loan was terminated. It has led the unemployment soared and the Germans struggled living in this unemployment situation. The depression also led to an opportunity to ideologist in introducing its ideology to meet the Germans need and wants at that time. The Nazi party officially the National Socialist German Worker's party (Nationalsozialistische Deutsche Arbeiterpartei-NSDAP) is one of an active party during 1920 - 1945. Recognizing the depression endured by many Germans in their own country, while Jewish Germans monopolised the economy, has resulted in ethnic cleansing (Holocaust) and total war. The party led by Adolf Hitler (Führer) and Joseph Goebbels as publicity minister, which plays a vital role in gaining public support for Nazi actions. As a result, the current study aims to examine the propaganda initiated by Goebbels, as one of the leaders in the Nazi inner circle, which led to the victory of the Nazi dictatorship. The evaluations concentrate on printed media such as posters, speeches, commoners joke and songs using applied propaganda model.